(untitled) (Scottish Historical and Archaeological Internet Reports, 2013)
A summary of earlier work in 1991 is followed by an archaeological description of the recent investigation. Five phases of activity have been identified, the earliest of which is represented by residual pottery sherds of 12th-century date. A large boundary ditch in phase 2 was cut in the 12th century and backfilled in the 13th. Phase 3 features included a grain-drying kiln, a wall and a number of pits. Phase 4 comprised 17th-century cultivation soils, a well and a possible cess pit. Phase 5 comprised 18th-and 19th-century cultivation soils and a cess pit.